2019
DOI: 10.1016/j.eururo.2019.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Trial of Adjuvant Radiotherapy Following Radical Prostatectomy Versus Radical Prostatectomy Alone in Prostate Cancer Patients with Positive Margins or Extracapsular Extension

Abstract: Background: It remains unclear whether patients with positive surgical margins or extracapsular extension benefit from adjuvant radiotherapy following radical prostatectomy. Objective: To compare the effectiveness and tolerability of adjuvant radiotherapy following radical prostatectomy. Design, setting, and participants: This was a randomised, open-label, parallel-group trial. A total of 250 patients were enrolled between April 2004 and October 2012 in eight Finnish hospitals, with pT2 with positive margins o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 22 publications
4
63
0
1
Order By: Relevance
“…Moreover, it should also be emphasized that 57.3% (70/122) in the observation group remained progression free [17]. Therefore, both our study and this recent trial support that observation followed by future radiation upon recurrence may provide an acceptable alternative to automatic early intervention with RT.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, it should also be emphasized that 57.3% (70/122) in the observation group remained progression free [17]. Therefore, both our study and this recent trial support that observation followed by future radiation upon recurrence may provide an acceptable alternative to automatic early intervention with RT.…”
Section: Discussionsupporting
confidence: 75%
“…Three trials, RADICALS-RT, GETUG-AFU 17 and RAVES were retained as being eligible for inclusion. Updated searches conducted in 2016 identified a further potentially eligible trial, however, this was subsequently excluded because it compared adjuvant RT to no RT, rather than with an early salvage policy (21). 6) and RADICALS-RT(5) trials were designed to assess whether ART was superior to SRT, the RAVES trial(7) was designed to assess whether SRT was non-inferior to ART in terms of biochemical failure.…”
Section: Resultsmentioning
confidence: 99%
“…For these patients undergoing immediate sRT, the pre-sRT PSA level appeared as a surrogate for RT efficacy pleading for a rapid initiation of RT, as demonstrated in the postsurgery BCR setting [12,17,19]. The Finnish randomized trial of postoperative RT also reported a significant BCR advantage for postoperative RT in the context of adverse features after RP (HR 0.26, 10-yr recurrence-free survival 82% in the RT arm vs 61% in the control arm) [32]. As no specific subgroup analysis was performed according to the postoperative PSA value, this study was not included in this systematic review.…”
Section: Discussionmentioning
confidence: 97%